Vrouwen die de wereld veranderen : gesprekken met Noreena Hertz, Vandana Shiva, Susan George, Naomi Klein en anderen - Goossens, Jesse (Rotterdam : Lemniscaat, 2004)
BMLIK
Nederlands
Monografie
Keywords: Brysse, Albert; vrouwen